2021
DOI: 10.1080/14740338.2021.1955100
|View full text |Cite
|
Sign up to set email alerts
|

The safety of current treatment options for advanced esophageal cancer after first-line chemotherapy

Abstract: The prognosis of advanced esophageal cancer (EC) remains poor, and few effective agents are available. For advanced EC patients, a combination of platinum and fluoropyrimidine is recognized as the standard first-line treatment. After first-line treatment, taxane or irinotecan has been used. Based on the KEYNOTE-181 and the ATTRACTION-3 trials, immune checkpoint inhibitors (ICIs) such as pembrolizumab and nivolumab appear to prolong survival, compared with cytotoxic agents, as second-line treatments for advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…At present, the first-line standard treatment is still based on fluorouracil combined with platinum-based chemotherapy, which has low overall efficiency and is prone to drug resistance after first-line chemotherapy and leads to disease progression. The publication of the KEYNOTE-181 and ATTRACTION-3 studies suggested that after failure of first-line chemotherapy in patients with esophageal squamous cancer, second-line immunotherapy has a significant overall survival (OS) benefit over chemotherapy, and based on this, the United States Food and Drug Administration (FDA) approved PD-1 blockade therapy pembrolizumab and nivolumab for second-line treatment of advanced esophageal squamous cancer ( 7 , 8 ).Given the clear survival benefit achieved with PD-1 in second-line treatment of esophageal squamous carcinoma, the subsequent KEYNOTE-590 study of PD-1 inhibitor pembrolizumab in combination with chemotherapy versus placebo in combination with chemotherapy in first-line use in advanced esophageal squamous carcinoma also confirmed a clear OS benefit of immunotherapy ( 9 ), suggesting that PD-1 in combination with chemotherapy is expected to be the first-line standard of care. Similarly, in head and neck squamous carcinoma, KEYNOTE-048 ( 10 ), and the subsequent CheckMate 141 and KEYNOTE-040 studies have demonstrated a significant OS benefit of second-line application of the immune checkpoint inhibitor PD-1 (either pembrolizumab or nivolumab) over standard therapy in metastatic or recurrent head and neck squamous carcinoma ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the first-line standard treatment is still based on fluorouracil combined with platinum-based chemotherapy, which has low overall efficiency and is prone to drug resistance after first-line chemotherapy and leads to disease progression. The publication of the KEYNOTE-181 and ATTRACTION-3 studies suggested that after failure of first-line chemotherapy in patients with esophageal squamous cancer, second-line immunotherapy has a significant overall survival (OS) benefit over chemotherapy, and based on this, the United States Food and Drug Administration (FDA) approved PD-1 blockade therapy pembrolizumab and nivolumab for second-line treatment of advanced esophageal squamous cancer ( 7 , 8 ).Given the clear survival benefit achieved with PD-1 in second-line treatment of esophageal squamous carcinoma, the subsequent KEYNOTE-590 study of PD-1 inhibitor pembrolizumab in combination with chemotherapy versus placebo in combination with chemotherapy in first-line use in advanced esophageal squamous carcinoma also confirmed a clear OS benefit of immunotherapy ( 9 ), suggesting that PD-1 in combination with chemotherapy is expected to be the first-line standard of care. Similarly, in head and neck squamous carcinoma, KEYNOTE-048 ( 10 ), and the subsequent CheckMate 141 and KEYNOTE-040 studies have demonstrated a significant OS benefit of second-line application of the immune checkpoint inhibitor PD-1 (either pembrolizumab or nivolumab) over standard therapy in metastatic or recurrent head and neck squamous carcinoma ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Palliative chemotherapy is often administered to patients with advanced-stage cancer. The standard chemotherapy agents for esophageal cancer include cisplatin, 5-fluorouracil, doxorubicin, capecitabine, docetaxel, irinotecan, oxaliplatin, paclitaxel, trifluridine-tripiracil, entrectinib, labrotrectinib, capecitabine, carboplatin, and leucovorin [12,13]. These drugs are usually given in combinations to improve their efficacies.…”
Section: Classic Treatment Of Esophageal Cancermentioning
confidence: 99%
“…Early-stage cancer treated with chemotherapy has shown improved survival rates, particularly in combination with radiation, while a poor prognosis is observed in advanced-stage esophageal cancer [15,16]. The continuous usage of the chemotherapeutic agent is characterized by dose-limiting cytotoxicity; drug resistance; and other adverse effects such as neuropathy, neutropenia, pneumonitis, bradycardia myelosuppression, thereby limiting the extensive use of these agents [13].…”
Section: Classic Treatment Of Esophageal Cancermentioning
confidence: 99%
“…Approximately ≥50% of the patients are diagnosed with stage IV disease and recurrence after primary curative intended therapy is also common. Hence the overall five-year survival rate of recurrent or metastatic disease remains below 5% [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, recommendations for the management of recurrent and metastatic disease are scare even in the national and oncological society guidelines [ 6 , 7 , 8 ]. Although within the last few years many trials have been conducted such as Keynote-181 and ATTRACTION-3 trial as well as phase III studies with irinotecan, docetaxel and Ramucirumab, the overall outcome remains highly unsatisfactory with ≤10 months of survival in patients failing to respond to first-line treatment [ 4 , 9 , 10 , 11 ]. This is even of more concern taking the quality of life (QoL) and required duration of therapy into consideration.…”
Section: Introductionmentioning
confidence: 99%